2008
DOI: 10.2495/eeia080151
|View full text |Cite
|
Sign up to set email alerts
|

Integrated assessment of flood protection measures in the context of climate change: hydraulic modelling and economic approach

Abstract: In order to protect our societies from damaging impacts of climate change (floods, heat waves, droughts etc), the most cost-effective adaptation measures must be selected among a wide range of options (including structural and nonstructural protection measures). The Belgian national project "ADAPT" aims to provide guidance for this choice by developing a decision-support tool for the selection of protection measures against increased risk resulting from climate change, and more specifically from floods. This t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Figure 10 represents the damage compared to the damage induced by the 100-year flood. More in-depth discussions of socio-economic impacts are presented separately (Coninx and Bachus 2007;Dewals et al 2008b;Ernst et al 2008a;Ernst et al 2008b;Ernst et al 2009b), whereas the scope of the present paper concentrates on the integrated methodology and the overall flow of data within the exposure and risk analyses.…”
Section: Economic Damagementioning
confidence: 99%
“…Figure 10 represents the damage compared to the damage induced by the 100-year flood. More in-depth discussions of socio-economic impacts are presented separately (Coninx and Bachus 2007;Dewals et al 2008b;Ernst et al 2008a;Ernst et al 2008b;Ernst et al 2009b), whereas the scope of the present paper concentrates on the integrated methodology and the overall flow of data within the exposure and risk analyses.…”
Section: Economic Damagementioning
confidence: 99%
“…The functions establish a relation between the level of water (i.e. flood magnitude) and the expected damages for specific building vulnerability classes (Thieken et al 2006;Dewals et al 2008;Jongman et al 2012). Nonetheless, there are some exceptions which account for further impact parameters such as flow velocity, water contamination, duration of inundation, individual precautionary behaviour, or early warning time (Cammerer et al 2013;Merz et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that compared to other types of natural hazards, floods are a considerable threat to a nation's economy, the built environment, and people (André et al, 2013;Kourgialas and Karatzas, 2012;Llasat et al, 2014;UNISDR, 2009). Furthermore, in recent decades, the probability of flood and the values of exposed properties have increased exponentially (Dewals et al, 2008;Elmer et al, 2012;Jalayer et al, 2013), which subsequently raises the significance of flood damage assessment. damage assessment in terms of mitigating the probability of expected losses is the main part of the risk management process (André et al, 2013;Elmer et al, 2010;Kaplan and Garrick, 1981), and the results will provide decision-makers, emergency management organisations, and insurance and reinsurance companies with a tool for planning better risk mitigation strategies to cope with future disasters (Emanuelsson et al, 2014;Merz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%